Psychometric Properties and Validation of the Arabic Academic Performance Rating Scale - Quadri, M. F. A. Q.; El-Kordy, M. S.; Moukhyer, M. E.; Mukhayer, A.; Ahmad, B. (Hindawi Publishing Corporation, 2017)
To validate the Arabic version of Academic Performance Rating Scale. Method. Translation and test-retest reliability were computed. Exploratory factor analysis and Rasch analysis were conducted to report on the validity. EFA factor structures were evaluated using a Scree plot and the standard multiple criteria included eigenvalue greater than 1. Average measures and step measures were ordered and themean-square outfit statistic for each category was also evaluated. Results. Cronbach’s Alpha value of 0.90 was obtained. No differences across category of educational levels were seen (